RANCANG PROGRAM APLIKASI PEMBELAJARAN TAJWID BERBASIS ANDROID - Reni Widyastuti (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The science of recitation is a science that studies or explains how to read the Qur'an properly and correctly. Allah SWT orders reading the Qur'an with tartil, that is, improving the reading of the letters of the Qur'an clearly, regularly and not in a hurry and knowing the places of endowments in accordance with the law of tajwid. The science of recitation aims to provide guidance on how to pronounce the correct verse so that the pronunciation and meaning are preserved. But in reality there are still many people who do not understand about reading the Qur'an properly and correctly for various reasons. One reason is not knowing the law of tajwid. In this research an Android-based Tajweed Science Learning Application has been built. This application uses Android Studio in the programming process. Android Studio is an IDE (Integrated Development Environment) for developing software and can be run on all platforms. The system modeling language used is UML (Unified Modeling Language). This application was created to make it easier for Muslims, be it children, teenagers or parents who have limited time to study with religious teachers, because this application can be used at any time, considering that mobile technology is currently widely used, especially android mobile